Identification, cloning, and immunological studies on a major eggplant (Solanum melongena L.) allergen Sola m 1: A new member of profilin allergen family. (February 2020) - Maity, Sukhendu; Bhakta, Subham; Bhowmik, Moumita; Sircar, Gaurab; Bhattacharya, Swati Gupta
Graphical abstract: Highlights: Sola m 1, a 17 kDa profilin is associated with Oral Allergy Syndrome (OAS) caused by eggplant. Sola m 1 is the major allergen showing 100% IgE-reactivity among the eggplant sensitized patients of Indian origin. Sola m 1 is monomeric, displays irreversible thermal denturation and its IgE-reactivity is lost after SGF digestion. Sola m 1 shows cross-reactivity with birch, rice, wheat, capsicum, peanut, and carrot. Sola m 1 is highly concentrated in eggplant seeds. Abstract: Eggplant or brinjal ( Solanum melongena L.) is widely consumed worldwide and thought to trigger allergic reactions in sensitive individuals. So far, no molecular information is available on the allergy-eliciting components of eggplant. In this study, a 17 kDa profilin, Sola m 1, was identified from eggplant by employing an immunoproteomic approach. Based on MALDI-TOF/TOF derived sequences, the full-length cDNA of Sola m 1 was PCR amplified and then cloned. Recombinant (r) Sola m 1 was expressed in E . coli and then purified by metal affinity and gel filtration. rSola m 1 reacted with IgE-antibodies in the sera from all eggplant allergic patients. rSola m 1 also displayed allergenic activity by stimulating histamine release. rSola m 1 was monomeric, and the CD spectra revealed it to be folded with a mixture of α-helices and β-strands. In the melting curve, rSola m 1 exhibited an irreversible denaturation where no refolding took place. Sola m 1 was found to share >80 % sequence identity with Bet v 2, which was further validated by confirming the presence of significant cross-reactivity with Bet v 2 in IgE-inhibition assay. IgE-cross reactivity was also observed between rSola m 1 and profilins from six other foods. In SGF assay, no rSola m 1-derived fragments exhibited IgE-reactivity after prolonged digestion suggesting the association of rSola m 1 with the oral allergy syndromes. Immunofluorescence localization revealed a high abundance of Sola m 1 allergen in eggplant seeds as compared to other edible parts. Taken together, Sola m 1 is the first major eggplant allergen reported in this study, which has the potential of being used as a candidate antigen in component-resolved diagnosis and immunotherapy.